On “Trade Induced Technical Change: The Impact of Chinese Imports on Innovation, IT, and Productivity” - Campbell, Douglas L; Mau, Karsten (Review of Economic Studies, 2021)
Abstract Bloom et al. (2016) find that Chinese import competition induced a rise in patenting, IT adoption, and total factor productivity (TFP) by up to 30% of the total increase in Europe in the late 1990s and early 2000s. We uncover several coding errors in an important robustness check of their patent results. When corrected, we find no statistically significant relationship between Chinese competition and patents. Other specifications in the original paper use a problematic $ \ log(1+\ rm patents) $ transformation. This normalization induces bias given low average patent counts for firms in China-competing sectors and rapidly declining patents across the sample.